Rwanda : Staff Report for 2019 Article IV Consultation and a Request for a Three-Year Policy Coordination Instrument-Press Release; Staff Report; and Statement by the Executive Director for Rwanda. (IMF Staff Country Reports; Country Report ;, 2019)
Rwanda has made considerable progress in sustaining high and inclusive growth and reducing poverty. Despite numerous shocks, macroeconomic management has been strong and debt risks have remained low. Going forward, the authorities' National Strategy for Transformation (NST) aims to make progress toward the SDGs, but its financing will be challenging. A more neutral medium-term fiscal policy stance can help, reinforced with commitments for more domestic revenue mobilization and mitigation of fiscal risks. The central bank moved to a new interest-rate based monetary policy framework and, with inflation below its target range, eased the policy stance. To support their policies and NST implementation, the authorities are requesting approval of a 3-year program supported by the Policy Coordination Instrument (PCI).